Controls on the diurnal streamflow cycles in two subbasins of an alpine headwater catchment. Issue 5 (8th May 2015) - Mutzner, Raphael; Weijs, Steven V.; Tarolli, Paolo; Calaf, Marc; Oldroyd, Holly J.; Parlange, Marc B.
Abstract In high‐altitude alpine catchments, diurnal streamflow cycles are typically dominated by snowmelt or ice melt. Evapotranspiration‐induced diurnal streamflow cycles are less observed in these catchments but might happen simultaneously. During a field campaign in the summer 2012 in an alpine catchment in the Swiss Alps (Val Ferret catchment, 20.4 km2, glaciarized area: 2%), we observed a transition in the early season from a snowmelt to an evapotranspiration‐induced diurnal streamflow cycle in one of two monitored subbasins. The two different cycles were of comparable amplitudes and the transition happened within a time span of several days. In the second monitored subbasin, we observed an ice melt‐dominated diurnal cycle during the entire season due to the presence of a small glacier. Comparisons between ice melt and evapotranspiration cycles showed that the two processes were happening at the same times of day but with a different sign and a different shape. The amplitude of the ice melt cycle decreased exponentially during the season and was larger than the amplitude of the evapotranspiration cycle which was relatively constant during the season. Our study suggests that an evapotranspiration‐dominated diurnal streamflow cycle could damp the ice melt‐dominated diurnal streamflow cycle. The two types of diurnal streamflow cycles were separated using a method based on the identification of the active riparian area and measurement of evapotranspiration.